Integrated management of anthracnose of snake gourd (Trichosanthes cucumerina L.) - Aswani Devi (Department of Plant Pathology,College of Agriculture, 2016)
The objective of present study entitled “Integrated management of anthracnose of snake gourd (Trichosanthes cucumerina L.)” was to make a comparative evaluation of foliar application of newer fungicides and biocontrol agents for the management of anthracnose disease of snake gourd. Surveys were conducted during October 2015 in snakegourd fields of five different locationsof Thiruvananthapuram district , viz., Instructional Farm, College of Agriculture,Vellayani, Department of Olericulture, College of Agriculture, Vellayani, Kalliyoor, Kakkamoola and Palapoor. Maximum disease incidence (90.00 per cent) and disease severity/ percentage disease index (44.22) were recorded in the snake gourd fields of Instructional Farm, Vellayani whereas disease parameters were minimum (21.89 per cent and 70.00 per cent) in the fields of Palapoor Pathogenicity tests revealed that the isolate C1 obtained from Instructional Farm, Vellayani produced maximum lesion size both on detatched leaf (2.53 cm2) as well as and on intact leaves of 30-days old potted plant (10.06 cm2). The smallest lesion size of 1.33 cm2 on detatched leaf and 1.53 cm2 on 30 days old potted plant was produced by the isolate C4 from Kakkamoola. Based on lesion size and virulence rating, C1 was screened as the most virulent isolate. Results of the cultural studies among the five isolates, showed that potato dextrose medium, oat meal medium and Richard’s medium were screened as the best media both in solid and liquid states for the growth of the tested isolates. Effect of different light sources (Fluorescent light: 253.7 - 185 nm, L.E.D light: 365 nm and UV light: 10 - 380 nm) on growth and sporulation of anthracnose pathogen indicated that the cultures exposed to fluorescent light and darkness for alternate cycles of 12 h of each day resulted in maximum mycelial growth and minimum days for sporulation for all the isolates. Growth was less when the cultures of the isolates were exposed to UV light for a period of 45 min. The morphological characters studied indicated that average conidial size of isolate C1, C2, C3 and C5 ranged from 11.40μm- 13.14μm x 4.48μm-4.82 µm and that they were cylindrical in shape with obtuse ends. The isolate C4 was ellipsoidal in shape and had a conidial size of 10.52μm x 4.40 µm. The isolates C1, C2, C3 and C5 were further identified at National Fungal Collection Culture India (NFCCI) - Pune, as C. coffeanum F.Noack and the isolate C4 was identified as C. musae (Berk. & M.A. Curtis) Arx. Isolate C1 of C. coffeanum which was earlier screened as the most virulent isolate was used for the subsequent studies conducted for the management of anthracnose disease in snake gourd. In the invitro assayconducted for screening of newer fungicides and bio control agents, effective for the inhibition of the isolate C1 of C. coffeanum, the nutrient potassium silicate (0.5 per cent) and fungicide mancozeb (0.4 per cent) resulted in hundred per cent mycelial inhibition while, KAU talc based formulations of the bio control agents viz., P. fluorescens (2 per cent) and T. viride (2 per cent) resulted in inhibition of 88.33 per cent and 87.33 per cent respectively and were selected for further evaluation in green house study. Minimum spore germination was recorded due to amendment of medium with T. viride (1.33 per cent). Conidia were also reduced in size when growth medium (PDA) were amended with tested chemicals and bio-control agents. In the green house studies using the snake gourd variety Kaumudi, maximum disease suppression was observed when plants were sprayed with 0.5 per cent potassium silicate (89.12 per cent) and 0.4 per cent of fungicide mancozeb (84.99 per cent) at fifteen days interval. Biometric parameters observed were also maximum for plants sprayed with 0.5 per cent potassium silicate followed by mancozeb and KAU talc based formulation of bio-control agents P. fluorescens and T. viride. Anthracnose affecting the foliage of snake gourd is a serious disease in snakegourd fields of Thiruvanathapuram district. The nutrient potassium silicate which was tested for the first time in Kerala against a plant pathogen, Colletotrichum sp. is found to be a promising chemical for management of the disease. The present study has also revealed the prospects of utilizing the mineral nutrient, potassium silicate for control of anthracnose disease as well as attainment growth promotion, flowering behavior, yield components and increases in yield of snake gourd which is an important vegetable crop of Kerala. Besides, this study also has highlighted the scope for integrating the fungicide mancozeb with bio-control agents like P. fluorescens and T. viride which were was also highly beneficial for the disease management as well as in improving the growth parameters of the crop under green house conditions. Such integration of fungicide mancozeb with bio-control agents will also be useful in minimizing the detrimental effects of continous and intensive use of this fungicide which is otherwise very effective in disease management. In the background of the promising results obtained from this thesis project especially from the use of potassium silicate, trials for confirming the beneficial effects of the treatments in field grown snake gourd plants would be useful for the vegetable growers in Kerala.